Pembuatan Logo Sebagai Corporate Identity Menggunakan Canva Pro Di UMKM Dapur G6 - Mohamad Arganta Adi Wicaksono; Heru utomo (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Dapur G6 promotes with word of mouth and through whatsapp. The purpose of this research is to create a logo as a corporate identity using Canva Pro at UMKM Dapur G6. This research uses the type of action research involving 15 respondents consisting of field supervisors, 2 computer experts, 2 marketing experts and 10 consumers. Based on logo measurements in accordance with good logo standards and from the results of distributing questionnaires, the average score is very effective. From the details of the average score, it can be concluded that making a logo as a corporate identity using Canva Pro can be declared very effective as a corporate identity.